(untitled) (Research, Society and Development, 2021)
The production of technological innovations from biomedical metallic materials exhibits extraordinary value for the reconstruction of structural tissues that have failed and thus, currently, titanium alloys with betagenic elements appear as an option, mainly to minimize the limitations regarding to elasticity module not only, but also, the cytotoxicity of widely traded alloys. The objective of this study was to perform scientific and technological indicators to outline the technological development environment of the type titanium alloys for the period from 2016 to 2020, by consulting the Scopus Elsevier data repository and the World Intellectual Property Organization - WIPO. The results showed that China, Brazil, India, Australia and Germany are the countries with the highest numbers of academic article publications on this subject. However, China and the United States of America are the countries that most deposited patent orders, each accounting for 27% of deposits.